Numerical study of radial force and equilibrium position of microscale spherical particle under the effect of inertial focusing in 2D microchannel - S. Natyanun (2020)
© Published under licence by IOP Publishing Ltd. Particle inertial focusing is a passive phenomenon at which a particle is acted upon by interaction with fluid and a channel wall, causing it to align at a certain distance from the channel wall called the equilibrium position as all transverse forces balance. In this work, numerical simulations using the finite element method were conducted in order to evaluate the forces acting on a spherical particle under Poiseuille flow in a 2D microchannel. Various fluid and particle parameters investigated include fluid density, viscosity, mean flow velocity, particle and channel dimensions. The calculated particle's equilibrium position in relation to each individual parameter is found to be proportional to the square of mean fluid velocity and fluid density, and the cube of particle size while inversely proportional to channel half-width and the square of fluid viscosity.